Silver nanoparticles immobilized on crosslinked vinyl polymer for catalytic reduction of nitrophenol: experimental and computational studies - Elsayed Elbayoumy; Ashraf A. El-Bindary; Tamaki Nakano; Mohamed M. Aboelnga (Scientific Reports)
Abstract The removal of toxic nitrophenols from the industrial wastewater is urgently needed from health, environmental and economic aspects. The present study deals with the synthesis of crosslinked vinyl polymer Poly(divinylbenzene) (poly(DVB)) through free radical polymerization technique using AIBN as initiator and acetonitrile as solvent. The prepared polymer was used as a support for silver nanoparticles via chemical reduction of silver nitrate on the polymer network. The prepared poly(DVB) and Ag/poly(DVB) composite were characterized by different techniques including Fourier transform infrared (FTIR) spectroscopy, thermogravimetric analysis (TGA), transmission electron microscopy (TEM), X-ray diffraction (XRD), and Brunauer Emmett-Teller (BET) analysis. The results exhibit that silver metal was well distributed on the surface of poly(DVB) without any aggregation as a nanocrystals with an average size 13 nm. Also, BET analysis confirm that Ag/poly(DVB) composite is a meso porous material with a surface area 127.428 m²/g. This composite was also applied as a heterogenous catalyst for the reduction of toxic nitrophenol in the industrial wastewater into a less toxic aminophenol with the aid of NaBH4 as reductant. In addition, Ag/poly(DVB) catalyst regards as one of the most active catalyst that exhibits an advantage over the other catalysts showing similar activities in the aspects that it can be more readily prepared than the competitors and that it works at the lowest concentration of NaBH4. Interestingly, DFT calculations were conducted to provide atomistic insights into the reduction mechanism and a detailed catalytic pathway have been proposed. Furthermore, the reusability experiment confirm that Ag/poly(DVB) was stable and can be removed from the reaction mixture by centrifuge and reused for four successive cycles with a slight decrease in their catalytic activity.